Sclerostin levels in patients with acromegaly - Arnika Wydra; Jakub Wydra; Jagoda Rogowska; Wojciech Zgliczyński; Izabella Czajka-Oraniec (Endokrynologia Polska)
Acromegaly is a rare, endocrine condition characterized by autonomous excessive secretion of growth hormone, causing numerous complications, including impairment of bone microarchitecture. The increased bone turnover observed in acromegaly can lead to bone fragility and elevated risk of vertebral fractures despite normal bone mineral density measured with dual-energy X-ray-absorptiometry. Treatment of acromegaly improves bone architecture; however, it does not completely reverse this process, and the increased vertebral fracture risk persists despite adequate disease control. Sclerostin, a product of the SOST gene, is one of the markers of bone turnover. Elevated sclerostin levels are correlated with impaired bone formation and serve as an independent risk factor for osteoporotic fractures in postmenopausal women. Inhibition of sclerostin is currently used in the treatment of osteoporosis in postmenopausal women. Considering the increased risk of vertebral fractures in patients with acromegaly, it is important to understand the potential role of sclerostin in this group of patients. This systematic review aimed to evaluate sclerostin levels in patients with acromegaly in comparison to the general population. The search strategy led to 7 studies meeting the inclusion criteria, which resulted in the inclusion of 385 patients with acromegaly in the final analysis. Available studies have provided conflicting results regarding sclerostin levels in acromegaly. Most of the studies showed lower sclerostin concentrations in patients with acromegaly compared to healthy controls, or no differences among groups. Only one study reported positive correlation between sclerostin levels and acromegaly, and its activity, expressed as insulin-like growth factor (IGF-1) and growth hormone (GH) concentrations. The rarity of acromegaly, small subject numbers, and heterogeneity of the groups could impact the results.